Architecture of Coastal Rural Houses in Thai Binh Province, Vietnam for Adaptation to Climate Change and Sea-Level Rise - Nguyen, Dinh Thi; Le, Hong Dan; Mai, Quang Khai (International Journal of Sustainable Construction Engineering and Technology, 2025)
In Thai Binh province, Vietnam, according to the RC4.5 climate change scenario by the end of the 21st century, sea levels are projected to rise by a maximum of 100 cm. This will result in the flooding of 22,313 hectares (66.13%) of Tien Hai District, 21,750 hectares (64.39%) of Kien Xuong District, and 26,756 hectares (47.94%) of Thai Thuy District. Such a rise in sea levels will significantly impact residential areas, housing, and agricultural production in the coastal villages of Thai Binh Province. The article’s aim is to propose architectural models for rural housing in these coastal hazard areas, allowing communities to adapt to climate change and sea-level rise. The goal is to help coastal residents continue living with inundation while ensuring a good quality of life and sustainable working conditions. The study uses field survey methods, document collection, data analysis, evaluation and computer simulation based on actual sea level rise to propose housing solutions. The article contributes proposes housing and shelter models for communities affected by rising sea levels, including houses with horizontally integrated shelter spaces in estuary areas, as well as houses with raised platforms and those integrating vertical shelter spaces in alluvial land areas.